Becoming minority: how discourses and policies produce minorities in Europe and India - Jyotirmaya Tripathy, Ed; Sudarsan Padmanabhan, Ed (Sage Publications India Pvt. Ltd., 2014)
"The present volume is intended to trace the processes through which minorities perform as minorities, their discursive formation, narrativization and representation. It is thus evident that the book moves away from an uncritical understanding of the term minority as a container of some unchanging core ideals, and leads to a framework where minority comes into existence in the very act of representation"--Provided by publisher.